Long-Term Effects of Public Low-Income Housing Vouchers on Work, Earnings, and Neighborhood Quality - Carlson, Deven; Haveman, Robert; Kaplan, Thomas; Wolfe, Barbara (My University, 2008)
This analysis of the federal Section 8 housing voucher program finds that voucher recipients live in better neighborhoods within five years of receiving vouchers. The results also show that voucher receipt initially causes lower earnings, but these dissipate over time. The work and earnings effects from voucher receipt differ substantially across demographic groups.